2009
DOI: 10.1093/neuonc/nop008
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the insulin-like growth factor-1 receptor by picropodophyllin as a treatment option for glioblastoma

Abstract: Glioblastoma (GB) is the most common malignant brain tumor in adults. It has limited treatment opportunities and is almost exclusively fatal. Owing to the central role the insulin-like growth factor-1 receptor (IGF-1R) plays in malignant cells, it has been suggested as a target for anticancer therapy including GB. The cyclolignan picropodophyllin (PPP) inhibits IGF-1R without affecting the highly homologous insulin receptor. Here, we show that PPP inhibits growth of human GB cell lines along with reduced phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 28 publications
5
88
0
1
Order By: Relevance
“…I-OMe-Tyrphostin AG 538 is an insulin growth factor 1 (IGF-1) receptor (IGF-1R) protein tyrosine kinase inhibitor. IGF-1 has been well discussed in GBM (13), and targeting IGF-1R has been studied as a treatment option for GBM (14). (-)-Perillic acid is a metabolite of perillyl alcohol (POH), which has shown a therapeutic anticancer effect and is currently under phase I and II clinical trials for human cancers including GBM (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…I-OMe-Tyrphostin AG 538 is an insulin growth factor 1 (IGF-1) receptor (IGF-1R) protein tyrosine kinase inhibitor. IGF-1 has been well discussed in GBM (13), and targeting IGF-1R has been studied as a treatment option for GBM (14). (-)-Perillic acid is a metabolite of perillyl alcohol (POH), which has shown a therapeutic anticancer effect and is currently under phase I and II clinical trials for human cancers including GBM (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…[96,97] Therefore, IGF-1R tyrosine kinase inhibitors or IGF-1 inhibitors, such as osthole, have been used to inhibit GBM proliferation, migration and EMT. [97,98] In a recent study of 218 cases of human GBM, IGF-1R overexpression was reported as an independent prognostic factor associated with shorter survival time and a less favorable response to temozolomide. [99] C-MET expression levels correlate with tumor grade in CNS malignancies, [100] and its activation also mediates EMTpromoting signals in cancer cells via class I A PI3K.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…(26) Inhibition of IGF-1R with PPP has been demonstrated in multiple myeloma, (23) breast cancer, (27) melanoma (28) and glioblastoma cells. (29) Although IGF-1R and the stimulatory ligands (IGF and insulin) are important for cancer proliferation, anti-IGF-1R therapy has not shown enough clinical benefits in randomized phase III trials. (30) The mediation of IGF-1R signaling in cancer cell is still unclear.…”
mentioning
confidence: 99%